AKTIVITAS DI PANTAI DALAM KARYA TAPESTRI - TATIS PUTRI, Drs. Erwin A, M.Sn., Dra. Ernis, M.Pd. (Universitas Negeri Padang, 2019)
Many activities that people often do while on vacation at the beach. One of them enjoys sunset (sunset), with various human activities. The creation of this work aims to visualize the beauty of the phenomenon of sunset with the activities of its people in tapestry work.Through the saumak technique and the giordes with 5 methods of creation of works (preparation, elaboration, synthesis, realization of concepts and research work, seven works were presented in the title. The title of the work: playing football, catching fish, fishing with boat, cheerful, inspired, returning home and barley sand.Keywords: activity, sunset, tapestry